Bioefficacy of diafenthiuron 50 WP from new source against sucking insect pests in Bt cotton - Zala, M B; Bhut, G D; Patel, C C; Ghetiya, L V; Bharpoda, T M; Borad, P K (Indian Journal of Plant Protection, 2020)
Field studies were conducted during two consecutive Kharif seasons of 2011 and 2012 in order to evaluate the bio-efficacy of diafenthiuron 50 WP from New source (NS) along with diafenthiuron 50 WP from Existing source (EX) @ 300 g a.i./ha and imidacloprid 17.8 SL @ 20 g a.i./ha as standard check against sucking pest complex of cotton. Diafenthiuron 50 WP (NS)@ 300 g a. i./ha was found highly effective in reducing the population of aphid, jassid, thrips and whitefly in cotton followed by imidacloprid 17.8 SL @ 20 g a.i./ha. The seed cotton yield was also recorded to be significantly highest in diafenthiuron 50 WP (NS)@ 300 g a.i./ha (32.5 q/ha) followed by imidacloprid 17.8 SL @ 20 g a.i./ha (30.2 q/ha) and diafenthiuron 50 WP (NS) @ 250 g a. i./ha. (30.1 q/ha). Considering the bio-efficacy and yield, diafenthiuron 50 WP (NS) @ 300 g a.i./ha was found effective against major sucking pests in Bt cotton.